Evaluación de las variables del desempeño cooperativo con enfoque en el buen vivir en la provincia de Carchi. - Meza Zambrano, Lorena E. (2018)
In Ecuador cooperatives emerged with the slogan of improving the socio-economic conditions and reduce knots of ingrained inequality from ancient times. The way that they are managed in social aspects was considered for the assessment of the cooperative performance variables, paying special attention to the Good Living. According to this, a procedure of three consecutive stages was structured: selection of the variables of the study, application of the assessment tool and the proposal of an improvement plan. In the first stage it collected information related to the subjects under study with the aim of solidifying in a general matrix the principles of good living, Popular and Solidarity Economy, Cooperative and Social Responsibility, in the stage two was applied the tool of evaluation of the existing variables to the cooperative performance measurement, then their results were tabulated and analyzed being subjected to refinement to be consulted by experts on topics of cooperative, these experts were elected by the kendall tool that measures the level of competition, immediately selected the appropriate variables with the help of the mathematical model torgerson and the Cronbach alpha that gave validation to The tool. In stage three was developed an improvement plan that will help to solve and reach an optimum level in its charge. It was concluded that the COAC in Carchi are framed in the fulfilment with the stipulated principles above, with the particularity that some indicators need to get better that are affecting their performance, raising corrective actions that will help the improvement of the same.